Rollover prevention for a heavy vehicle using optimised slide mode steering control. (29th July 2019) - Jin, Zhilin; Wang, Chao; Zhang, Lei; Zhao, Wanzhong; Khajepour, Amir
For a heavy vehicle, active steering can effectively prevent rollover, however, it also changes the operation of the vehicle away from the driver's intentions. To improve rollover stability and reduce tracking error, an optimised slide mode steering control strategy is proposed. Four degrees of freedom linear model is used, which includes lateral, yaw, and roll motions of the sprung mass and unsprung mass. This model is also validated to describe heavy vehicle rollover dynamics. From the model, slide mode control based roll angle and lateral displacement strategies are developed, respectively, and the optimised slide mode steering control strategy is presented to track the set routes and prevent vehicle rollover. Furthermore, some typical numerical cases are simulated to demonstrate the effectiveness of the control strategies. The results show that the optimised strategy can effectively prevent vehicle rollover and significantly improve the performance of tracking the driver's intention for a heavy vehicle.